Association of Chronic Obstructive Pulmonary Disease Severity with Cutaneous Manifestations and Systemic Inflammatory Biomarkers. A Cross-Sectional Clinical Study - Kashif Sardar, Nighat Fatima, Saba Amin, Sufyan Saleem Safdar, Zahid Habib Qureshi, Bakhtawar Farooq (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a chronic inflammatory disease of the respiratory system with considerable extrapulmonary manifestations, such as dermatologic abnormalities. Chronic hypoxia and chronic systemic inflammation could play a role in the pathogenesis of multiple skin changes in patients with COPD. There is, however, limited data on the correlation between skin manifestations and systemic inflammatory biomarkers and the severity of the COPD. Objective: To assess the relationship between COPD severity and inflammatory serum markers and cutaneous findings in patients with COPD. Methods: The cross-sectional clinical study was performed from January 2022 to January 2023 at the Department of Pulmonology and Department of Dermatology, Multan Medical & Dental College. Consecutive non-probability sampling was done, and 150 patients with clinically and spirometrically diagnosed COPD were included. Severity of COPD was determined based on Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines. A detailed dermatological examination was conducted to look for skin signs. Standard laboratory techniques were used for the measurement of serum levels of C-reactive protein (CRP), Interleukin-6 (IL-6), tumour necrosis factor-alpha (TNF-α), erythrocyte sedimentation rate (ESR) and fibrinogen. SPSS software version 26.0 was used to analyze the data. Results: The mean age of participants was 60.9 ± 8.7 years, with male predominance (67.3%). The most frequent cutaneous manifestations were xerosis (46.0 %), hyperpigmentation (36.0 %), pruritus (32.7 %), nail clubbing (27.3 %) and cyanosis (23.3 %). The dermato-logical abnormalities were significantly higher in severe and very severe COPD patients than in the mild and moderate disease groups (p<0.05). Systemic inflammatory biomarkers including CRP, IL-6, TNF-α, ESR, and fibrinogen showed significant progressive elevation with increasing COPD severity (p<0.001). Strong positive correlation with inflammatory biomarker and the number of cutaneous manifestations was seen. Conclusion: There is a marked association between the severity of COPD and systemic inflammatory activity and the frequency of cutaneous manifestations. Skin problems can be a valuable clinical sign of systemic inflammation and disease activity in COPD. Keywords: Chronic Obstructive Pulmonary Disease; COPD; cutaneous manifestations; systemic inflammation; inflammatory biomarkers; IL-6; TNF-α; dermatology; pulmonary disease; CRP.